Konsep Dasar Motivasi Belajar - Raskita Enjelika Manik; Delima Hot Marito Hasugian; Herda Sitanggang; Helena Turnip (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The purpose of this writing is to find out about the basic concepts in learning motivation. By using qualitative research methods, with a literature review approach. Understanding the concept of learning motivation is very important, especially for educators because it can help in creating a supportive and effective learning environment. Learning motivation is the foundation for a student in achieving academic success. Without strong motivation, the teaching and learning process will not take place optimally. Therefore, learning motivation has become a very relevant topic of study for educators, psychologists, and education observers around the world. In this work, readers will be presented with a comprehensive understanding of the concept of learning motivation, the theories that underlie it, and the factors that influence motivation in the context of education. In learning activities, motivation can be said to be the overall driving force within a person that gives rise to learning activities, which guarantees the continuity of learning activities and provides direction to learning activities, so that the goals desired by the learning subject can be achieved.